Comparison of Clinical Outcomes of Periprosthetic Fractures Between Cemented vs Cementless Stem Methods After Initial Total Hip Arthroplasty or Bipolar Hemiarthroplasty: A Multicenter Analysis (TRON Study) - Hiroaki Tachi, MD; Yasuhiko Takegami, MD; Toshiaki Okura, MD, PhD; Katsuhiro Tokutake, MD, PhD; Hiroaki Nakashima, MD, PhD; Kenichi Mishima, MD, PhD; Takehiro Kasai, MD, PhD; Shiro Imagama, MD, PhD (Arthroplasty Today, 2025)
Background: Periprosthetic femoral fractures are challenging complications after total hip arthroplasty (THA) or bipolar hemiarthroplasty (BHA). This multicenter study compared clinical outcomes of surgical periprosthetic femoral fracture (PFF) treatment following initial implantation of cemented vs cementless femoral stems. Methods: This retrospective multicenter study included 201 patients from multiple hospitals who had PFFs treated surgically between 2010 and 2022. They were divided into THA (n = 71) and BHA (n = 130) cohorts based on initial arthroplasty. Clinical outcomes of mortality, radiographic bone union, operative metrics, and complications were compared after the patients were matched for age. Results: In the matched THA cohorts (n = 15 each), there were no significant differences in mortality, bone union, operative time, blood loss, or complications between cemented and cementless stems. In the matched BHA cohorts (n = 27 each), mortality and bone union were similar, but cementless stems showed higher intraoperative blood loss. Furthermore, Type B fractures were more common with cementless stems, whereas Type C fractures were predominated with cemented stems. Conclusions: Among patients who underwent THA or BHA, mortality and bone union following treatment of PFFs did not differ between cemented and cementless stems. However, patients who underwent BHA with cementless stems required longer operations and lost more blood. Type B fractures requiring revision occurred more frequently with cementless stems, whereas Type C fractures treated with open reduction and internal fixation were more frequent with cemented stems, which thus influenced perioperative factors. Cement use for initial arthroplasty was associated with certain favorable characteristics and positive treatment outcomes of PFFs.